Cars that Provide Pleasure: a study about the connection between attributes and personal values of buyers from São Paulo - Piato, Éderson Luiz; Pimenta, Márcio Lopes; Fowler, Fábio Roberto (Review of Business Management, 2014)
The objective of this paper is to evidence the cognitive structure of the values of automobile consumers from São Paulo, considering two models (one compact and another sportive) of a car maker. Specifically, this paper aimed to identify elements through a hierarchical value map (HVM), the attributes, the consequences and the values that characterize the perceptions of the consumers and respective connections among these. Therefore, thirty in depth interviews were performed with buyers of the two models. The qualitative Laddering technique (REYNOLDS; GUTMAN, 1988), based on the Means-End Chain Theory (GUTMAN, 1982), guided the collection, analysis and interpretations of data. The results point out that personal values are determinant aspects for the decision of buying such models and, consequently, should be considered for the elaboration of strategies of automobile design and communication. The analysis of the HVM highlighted that the main chains, for the two models, are started by the attributes: “internal trim” and “Design”. These items generate the perception of the value “Hedonism” - the most expressive state for the interviewees. This highlights the importance of this value in deciding to buy those two analyzed models.